Neuroinflammation Treatment via Targeted Delivery of Nanoparticles - Cerqueira, Susana R.; Ayad, Nagi G.; Lee, Jae K. (Frontiers in Cellular Neuroscience, 2020)
The lack of effective treatments for most neurological diseases has prompted the search for novel therapeutic options. Interestingly, neuroinflammation is emerging as a common feature to target in most CNS pathologies. Recent studies suggest that targeted delivery of small molecules to reduce neuroinflammation can be beneficial. However, suboptimal drug delivery to the CNS is a major barrier to modulate inflammation because neurotherapeutic compounds are currently being delivered systemically without spatial or temporal control. Emerging nanomaterial technologies are providing promising and superior tools to effectively access neuropathological tissue in a controlled manner. Here we highlight recent advances in nanomaterial technologies for drug delivery to the CNS. We propose that state-of-the-art nanoparticle drug delivery platforms can significantly impact local CNS bioavailability of pharmacological compounds and treat neurological diseases.